2021
DOI: 10.6007/ijarbss/v11-i1/8471
|View full text |Cite
|
Sign up to set email alerts
|

The Signaling Effect of Dividends on The Market & Financial Performance of Listed Companies in Sri Lanka

Abstract: This study aims to examine the Signaling effect of dividends on the financials and market performance of listed companies in Sri Lanka. This study facilitates information regarding current and future performances, such as dividend practices, future growth projections and insights into market behaviour for stakeholders. The total population was identified as the companies listed in the CSE, which was approximately 316 firms. The sample of the study was 102 companies listed between the years 2015 to 2019. System… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Findings support the idea that the dividend payout is a non-relevant fact that affects financial performance. The results are similar to Thafani and Abdullah (2014) and Karunarathne et al (2021) found that DPR has a statistically insignificant relationship with financial performance. That indicates profitability has not increased with the dividend increase of the listed manufacturing, food, beverage & tobacco companies in Sri Lanka.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Findings support the idea that the dividend payout is a non-relevant fact that affects financial performance. The results are similar to Thafani and Abdullah (2014) and Karunarathne et al (2021) found that DPR has a statistically insignificant relationship with financial performance. That indicates profitability has not increased with the dividend increase of the listed manufacturing, food, beverage & tobacco companies in Sri Lanka.…”
Section: Discussionsupporting
confidence: 88%
“…The study aimed to establish the relationship between dividend policy and firm financial performance in manufacturing, food, beverage, and tobacco companies. Employing methods consistent with prior research (Amindu 2007;Karunarathne et al 2021;Thafani & Abdullah 2014), descriptive statistics, correlation, and panel regression were conducted. However, the first hypothesis, indicating no statistically significant connection between the Dividend Payout Ratio (DPR) and company financial performance, was rejected as the p-value of regression analysis was less than 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations